The survey of awareness of hospitalized mothers in postpartum ward regarding pregnant women\'s rights charter and its related factors in the governmental hospitals of Sanandaj City in 2013 - Leyla Hasheminasab; Ronak Shahoee; Farzaneh Zaheri; Sirous Shahsavari (Kurdistan University of Medical Sciences, 2015)
Background and Aim: pregnancy and child birth is one the periods that women face throughout their lives. Mothers and families should be aware of the rights of pregnant women due to the problems and challenges of this period. Therefore, this study was designed to determine the level of awareness of the hospitalized mothers in postpartum ward about the pregnant women's rights charter in the governmental hospitals of Sanandaj city in 2013.  Materials and Methods: This was a cross-sectional study in which 840 pregnant women after childbirth in the post partum ward of a governmental hospital participated. The sampling method was convenience sampling and the data collection tool was a questionnaire consisted of two parts personal information and pregnant women's rights charter and its reliability was determined by test-retest reliability. The data were analyzed by SPSS20 software and chi-square and T tests. Findings : The results indicated the desirability of mothers' knowledge of their physical and psycho-social rights.  The relationship between awareness of mothers with jobs was only (P<0.019) and with husband’s education level was (P<0.003). But the awareness of mothers about privacy, visiting the place of delivery during pregnancy, obtaining consent and having hospital’s document after discharge was not desirable. Conclusion: considering the results of the study which represents the efficient role of men in awareness of women, holding educational classes and training for men to promote family health level is effective.